The State in Classical Laissez-Faire, Its Crisis, and the Establishment of Fordism - Bonanno, Alessandro (The Legitimation Crisis of Neoliberalism, 2017)
This chapter stresses the point that contrary to arguments proposed by neoliberals, the state has consistently been a relevant actor in the organization of the economy and society. It indicates that the role played by the state was fundamental in the expansion and stability of capitalism in its early stages, during the laissez-faire era of the nineteenth century and under Fordism in the twentieth century. This argument is illustrated through a review of salient aspects of classical liberal theories of the state such as those of John Locke, Adam Smith, Jeremy Bentham, and John Stuart Mill and a brief review of the theory of Marx and early twentieth century contributions such as those of Karl Polanyic and John M. Keynes. An analysis of the theories of the role of the state under Fordism is proposed in the final sections of the chapter.
Keywords: Fordism; MARX, Karl, 1818-1883; double movement; economic sociology; organizational studies; regulated capitalism

Nancy Fraser and Karl Polanyi. A Possible Dialogue - Brie, Michael (Karl Polanyi in Dialogue: A Socialist Thinker for our Times, 2017)
From the very beginning a misunderstanding has to be cleared up – the reduction of Polanyi’s work to that of a reformer who wants to counter the excesses of market radicalism with social protective measures and believes that the crisis of modern
Keywords: FRASER, Nancy; triple movement